Gene expression analysis reveals novel altered genes in nasal polyps - Babeto, Erica [UNESP]; Calmon, Marilia de Freitas [UNESP]; Scarin Provazzi, Paola Jocelan; Colombo, Jucimara; Cordeiro, Jose Antonio; Bonilha, Jane Lopes; Fernandes, Atilio Maximino; Rahal, Paula [UNESP] (Spandidos Publ Ltd, 2010)
Nasal polyposis (NP) is a chronic inflammatory disease of the nasal mucosa characterized by the infiltration of inflammatory cells, mainly eosinophils. Although nasal polyposis occurs in 4% of the population, its physiopathology remains unclear. The aim of this study was to identify and characterize differentially expressed genes that can be used in the prognosis: treatment and elucidation of this physiopathology. To identify novel genes differentially expressed in NP, we applied real-time quantitative PCR to 11 NP samples and to a pool of total RNA from a subset of 13 normal nasal mucosa samples from human autopsies. For selecting genes, the methylated CpG island amplification technique was used. Five differentially methylated clones (ATP2A1, NOVA1, PLCD3, SOLH and TGF beta 1) were identified. However, these genes presented methylated CpG islands between exons, i.e., not in the promoter regions of the genes. Thus, as shown by real-time PCR, the ATP2A1, SOLH, PLDC3 and TGF beta 1 genes were overexpressed in NP. The genes identified in this study are probably involved in some stage of the process of formation and development of nasal polyposis, as they were highly expressed in the nasal polyp samples.
Keywords: ATP2A1; Gene expression; nasal polyps; NOVA1; methylated CpG island amplification; PLCD3; Real-time PCR; SOLH; TGF beta 1